Active material, all-solid-state battery, and method for producing active material
By using specific Si-based active substances in all-solid batteries, and using specific peak intensity ratios and ranges in infrared spectrum to suppress volume changes in the electrode layer, the problem of large volume changes in Si-based active substances during charging and discharging is solved, and higher durability and energy density are achieved.
Patent Information
- Application Number
- CN202111253163.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-11-11
- Filing Date
- 2021-10-27
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2041-10-27
AI Technical Summary
The volume of the Si-based active substance changes greatly during the charge and discharge process, resulting in a decrease in durability and energy density of the electrode layer.
An active substance for an all-solid battery containing at least Si is provided to suppress electrode layer volume changes during charge and discharge by a specific peak intensity ratio (I2/I1) and a single peak intensity range (0.55≤I2/I1≤1.0 and 0.01≤I1≤0.08) in the infrared spectrum. The active material may have a type II silicon closure, a type I silicon closure, and a diamond-type Si crystal phase, and form a void inside the particles.
By using this active substance, the volume change of the negative electrode layer during charging and discharging can be effectively suppressed, the durability and energy density of the battery can be improved, and the size of the constraint fixture can be reduced.
Smart Images

Figure CN114551847B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to an active material, an all-solid-state battery, and a method for producing the active material. Background Art
[0002] A fully solid-state battery is a battery having a solid electrolyte layer between a positive electrode layer and a negative electrode layer, which has the advantage of being easy to simplify safety devices compared to a liquid-based battery having an electrolyte containing a flammable organic solvent. In addition, Si-based active materials are known as active materials used in fully solid-state batteries. For example, Patent Document 1 discloses a sulfide fully solid-state battery negative electrode having a negative electrode active material layer, the negative electrode active material layer containing at least one material selected from Si and Si alloys as a negative electrode active material.
[0003] In addition, Patent Document 2 discloses a silicon oxide structure comprising a silicon oxide skeleton containing Si and O in its atomic composition and silicon nanoparticles chemically bonded to the silicon oxide skeleton as constituent elements. Patent Document 2 also records that in a spectrum measured by infrared spectroscopy, the -1 The intensity of the peak 1 (I1) of the Si-H bond is similar to that of the peak 2 at 1000-1200 cm -1 The ratio (I1 / I2) of the intensity of peak 2 (I2) of Si-O-Si bond is within a predetermined range.
[0004] Patent Document 3 discloses SiOx (negative electrode active material for lithium ion secondary battery) having a wavelength of 3400 to 3800 cm-1 in a spectrum measured by an infrared spectrometer. -1 The intensity of the peak A1 of the silanol group is similar to that of the peak A2 at 1000-1200 cm -1 The value A1 / A2 of the ratio of the intensity of the peak A2 of the siloxane bond is 0.1 or less.
[0005] Patent Document 4 discloses a negative electrode active material having a mother particle composed of silicon oxide and a coating layer composed of a conductive carbon material and covering at least a portion of the surface of the mother particle, wherein the negative electrode active material has a surface area of 600 cm-1 obtained by infrared spectroscopy. -1 ~1400cm -1 The maximum peak intensity of the infrared absorption spectrum is set to 1 at 900 cm -1 The strength is 0.30 or more.
[0006] Prior art literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2018-142431
[0008] Patent Document 2: Japanese Patent Application Publication No. 2019-119638
[0009] Patent Document 3: Japanese Patent Application Publication No. 2011-108635
[0010] Patent Document 4: International Publication No. 2014 / 119238 Summary of the invention
[0011] Si has a large theoretical capacity and is effective for high energy density of batteries. On the other hand, Si has a large volume change during charge and discharge. Therefore, the volume change of the electrode layer using Si is large during charge and discharge. The present disclosure is completed in view of the above actual situation, and its main purpose is to provide an active material that can suppress the volume change of the electrode layer during charge and discharge.
[0012] In the present disclosure, an active material for an all-solid-state battery is provided, which contains at least Si and has a wavelength of 900 cm -1 Over 950cm -1 The maximum peak intensity below is set as I1, and 1000cm -1 Over 1100cm -1 When the following maximum peak intensity is defined as I2, the above I1 and the above I2 satisfy 0.55≤I2 / I1≤1.0 and 0.01≤I1.
[0013] According to the present disclosure, the value of I2 / I1 is within a predetermined range, and the value of I1 is also within a predetermined range, so that an active material capable of suppressing a volume change of the electrode layer during charge and discharge can be obtained.
[0014] In the above disclosure, the above I1 may satisfy 0.02≤I1≤0.08.
[0015] In addition, the present disclosure provides an active material for an all-solid-state battery, which contains at least Si and has a wavelength of 900 cm -1 Over 950cm -1 The maximum peak intensity below is set as I1, and 1000cm -1 Over 1100cm -1 When the following maximum peak intensity is defined as I2, the above I1 and the above I2 satisfy 0.55≤I2 / I1≤1.0 and 0.01≤I2.
[0016] According to the present disclosure, the value of I2 / I1 is within a predetermined range, and the value of I2 is also within a predetermined range, so that an active material capable of suppressing a volume change of the electrode layer during charge and discharge can be obtained.
[0017] In the above disclosure, the above I2 may satisfy 0.02≤I2≤0.08.
[0018] In the above disclosure, the above active material may have at least one of a crystal phase of a type II silicon clathrate, a crystal phase of a type I silicon clathrate, and a diamond-type Si crystal phase.
[0019] In the above disclosure, the above active material may have voids inside the primary particles.
[0020] In addition, the present disclosure provides an all-solid-state battery including a positive electrode layer, a negative electrode layer, and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer, wherein the negative electrode layer contains the active material and a solid electrolyte.
[0021] According to the present disclosure, by using the above-mentioned active material, it is possible to obtain an all-solid-state battery capable of suppressing the volume change of the negative electrode layer during charge and discharge.
[0022] In addition, the present disclosure provides a method for manufacturing an active material, which is a method for manufacturing the above-mentioned active material, comprising a synthesis step, a washing step and a drying step, wherein a first precursor is synthesized in the above-mentioned synthesis step, and the above-mentioned first precursor is washed with an organic solvent or acid having a relative dielectric constant of 5 or more to obtain a second precursor in the above-mentioned washing step, and the above-mentioned second precursor is dried by heat in the above-mentioned drying step to obtain the above-mentioned active material.
[0023] According to the present disclosure, by washing the first precursor with an organic solvent or acid having a high relative dielectric constant and then drying it, an active material capable of suppressing the volume change of the electrode layer during charge and discharge can be obtained.
[0024] In the above disclosure, the above organic solvent may be a ketone.
[0025] In the above disclosure, the above synthesis process may include an alloying treatment step and a Li removal treatment step. In the above alloying treatment step, the intermediate is alloyed with a Li-based material to obtain an alloy compound. The above intermediate has at least one of a crystal phase of a type II silicon inclusion compound, a crystal phase of a type I silicon inclusion compound, and a diamond-type Si crystal phase. In the above Li removal treatment step, Li is removed from the above alloy compound to form voids inside the primary particles.
[0026] In the above disclosure, in the Li removal treatment step, ethanol may be used to remove the Li from the alloy compound.
[0027] In the present disclosure, there is an effect that an active material capable of suppressing a volume change of an electrode layer during charge and discharge can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic three-dimensional diagram illustrating the Si crystal phase.
[0029] Figure 2This is a schematic cross-sectional view illustrating an all-solid-state battery in the present disclosure.
[0030] Figure 3 This is a flow chart illustrating the method for producing the active material in the present disclosure.
[0031] Figure 4 This is a flow chart illustrating a method for synthesizing the first precursor in the present disclosure.
[0032] Figure 5 These are the results of IR measurement of the active materials obtained in Examples 1 and 2 and Comparative Examples 1 to 3.
[0033] Description of Reference Numerals
[0034] 1… Positive electrode layer
[0035] 2…Negative electrode layer
[0036] 3…Solid electrolyte layer
[0037] 4…Positive electrode collector
[0038] 5…Negative electrode collector
[0039] 10…All-solid-state batteries DETAILED DESCRIPTION
[0040] Hereinafter, the active material, the all-solid-state battery, and the method for producing the active material in the present disclosure will be described in detail.
[0041] A. Active substances
[0042] The active material disclosed in the present invention is an active material used in an all-solid-state battery, contains at least Si, and has a wavelength of 900 cm-1 in the infrared spectrum. -1 Over 950cm -1 The maximum peak intensity below is set as I1, and 1000cm -1 Over 1100cm -1 When the following maximum peak intensity is defined as I2, 0.55≤I2 / I1≤1.0 is satisfied. I1 may satisfy 0.01≤I1. Similarly, I2 may satisfy 0.01≤I2.
[0043] According to the present disclosure, the value of I2 / I1 is within a predetermined range, and the value of I1 or I2 is also within a predetermined range, so an active material that can suppress the volume change of the electrode layer during charge and discharge can be obtained. As mentioned above, Si has a large theoretical capacity and is effective for high energy density of the battery. On the other hand, Si has a large volume change during charge and discharge. If the volume change during charge and discharge is large, it will have adverse effects such as reduced durability and reduced energy density caused by the large-scale restraining fixture. Since the large volume change of Si particles themselves is the biggest problem, the volume change of the electrode layer is mostly suppressed by limiting the utilization of Si particles. However, if the use of Si particles is limited, it is difficult to seek to improve energy density.
[0044] Therefore, the inventors have previously studied the provision of voids inside Si particles and the use of inclusion Si particles in order to reduce the volume change of Si particles. On the other hand, the inventors have obtained the following insights: as the reason for the increase in the volume change of the electrode layer, the aggregation of Si particles in the electrode layer plays a role. Therefore, focusing on the functional groups and compounds present on the surface of Si particles, it is found that by controlling the surface state of Si particles (specifically, increasing the polarity of the surface of Si particles), the aggregation of Si particles can be suppressed and the volume change of the electrode layer can be reduced. It is speculated that the reason for suppressing the aggregation of Si particles is that by increasing the polarity of the surface of Si particles, the affinity with solid electrolytes with high polarity generally becomes good, and when the electrode layer is made, the Si particles are uniformly dispersed. It is presumed that the Si particles are uniformly dispersed, and the contact area between the Si particles and the solid electrolyte is increased, thereby making the charge and discharge reactions in the electrode layer uniform, and as a result, the volume change of the electrode layer can be suppressed.
[0045] The active substance disclosed herein has an I2 / I1 ratio within a predetermined range in an infrared spectrum (IR spectrum). I1 is at 900 cm -1 Over 950cm -1 The maximum peak intensity below is usually due to the peak of Si-R (R is a hydrophobic functional group such as CH3) present on the surface of the active material. -1 Over 880cm -1 The following ranges sometimes appear from CO3 2- Even if we assume that in CO3 2- When the peak of CO3 moves to the high frequency side, I1 does not correspond to 2- In addition, I1 can also be at 850cm -1 Over 950cm -1 The following are the intensities of the peaks derived from Si-R.
[0046] I2 is at 1000cm -1 Over 1100cm-1 The maximum peak intensity below is usually derived from the peak of Si-O-Si on the surface of the active material. In addition, the peak derived from Si-O-Si is usually broad, so it may not be possible to confirm a clear peak. Considering this situation, at 1000cm -1 Over 1100cm -1 The maximum peak intensity below 1000cm -1 Over 1100cm -1 The following is handled at maximum intensity.
[0047] In the present disclosure, the value of I2 / I1 is generally above 0.55, and may be above 0.60, or above 0.65. On the other hand, the value of I2 / I1 is generally below 1.0, or below 0.95. In addition, I1 is generally above 0.01, and may be above 0.02, or above 0.03. On the other hand, I1 is, for example, below 0.08, or below 0.06. In addition, I2 is generally above 0.01, and may be above 0.02, or above 0.03. On the other hand, I2 is, for example, below 0.08, or below 0.06. The infrared spectrum (IR spectrum) in the present disclosure is a spectrum obtained by the ATR method (total reflection measurement method). In addition, the intensity in the IR spectrum represents absorbance.
[0048] The active material in the present disclosure preferably has at least one of a crystal phase of a type II silicon inclusion compound, a crystal phase of a type I silicon inclusion compound, and a diamond-type Si crystal phase. In addition, the active material preferably has any one of the above crystal phases as a main phase. The so-called "having as a main phase" means that the peak belonging to the above crystal phase is the peak with the largest diffraction intensity among the peaks observed in the X-ray diffraction measurement.
[0049] The active material in the present disclosure may have a type II silicon inclusion compound crystal phase. Figure 1 As shown in (a), in the crystal phase of type II silicon inclusion compound, a polyhedron (cage) containing pentagons or hexagons is formed by multiple Si elements. The polyhedron has a space inside it that can accommodate metal ions such as Li ions. By inserting metal ions into this space, the volume change caused by charging and discharging can be suppressed. In particular, in all-solid batteries, in order to suppress the volume change caused by charging and discharging, it is generally necessary to apply a high constraint pressure, but by using the active material in the present disclosure, it is possible to seek to reduce the constraint pressure, and as a result, the large-scale constraint fixture can be suppressed.
[0050] The crystal phase of type II silicon inclusion complex usually belongs to the space group (Fd-3m). In the X-ray diffraction measurement using CuKα rays, the crystal phase of type II silicon inclusion complex has typical peaks at 2θ=20.09°, 21.00°, 26.51°, 31.72°, 36.26°, and 53.01°. These peak positions can move back and forth within the range of ±0.50°, can move back and forth within the range of ±0.30°, and can also move back and forth within the range of ±0.10°.
[0051] In the crystal phase of type II silicon inclusion compound, the peak at 2θ=20.09°±0.50° is defined as peak A, and the peak at 2θ=31.72°±0.50° is defined as peak B. In addition, the intensity of peak A is defined as I A , the intensity of peak B is taken as I B On the other hand, the maximum intensity at 2θ = 22° to 23° is taken as I M When 2θ=22° to 23°, since the peak of the crystal phase related to Si generally does not appear in the range, it can be used as a reference.
[0052] Preferred I A / I M The value of is greater than 1. A / I M When the value of is 1 or less, it can be judged that the crystal phase of the type II silicon inclusion compound is not substantially formed. A / I M The value of is, for example, 2 or more, 5 or more, or 7 or more. A / I M There is no particular upper limit on the value of A / I M The value of is 1000 or more).
[0053] Preferred I B / I M The value of is greater than 1. B / I M When the value of is 1 or less, it can be judged that the crystal phase of the type II silicon inclusion compound is not substantially formed. B / I M The value of is, for example, 2 or more, or 5 or more. B / I M There is no particular upper limit on the value of B / I M The value of is 1000 or more).
[0054] The active material in the present disclosure has a crystal phase of a type II silicon inclusion compound, and may not have a diamond-type Si crystal phase described later. "Not having a crystal phase" can be confirmed by not confirming a peak of its crystal phase in an X-ray diffraction measurement. In addition, the active material in the present disclosure has a crystal phase of a type II silicon inclusion compound, and may not have a crystal phase of a type I silicon inclusion compound described later.
[0055] The active material in the present disclosure may also have a crystal phase of type I silicon inclusion compound. Figure 1 As shown in (b), in the crystal phase of the type I silicon clathrate, similarly to the type II silicon clathrate, a plurality of Si elements form polyhedrons (cages) including pentagons or hexagons, and thus the volume change due to charge and discharge can be suppressed.
[0056] The crystal phase of type I silicon inclusion complex usually belongs to the space group (Pm-3n). In the X-ray diffraction measurement using CuKα rays, the crystal phase of type I silicon inclusion complex has typical peaks at 2θ=19.44°, 21.32°, 30.33°, 31.60°, 32.82°, 36.29°, 52.39°, and 55.49°. These peak positions can move back and forth within the range of ±0.50°, can move back and forth within the range of ±0.30°, and can also move back and forth within the range of ±0.10°.
[0057] The active material in the present disclosure may have a diamond-type Si crystal phase. Figure 1 As shown in (c), ordinary Si has a diamond-type crystal phase. In the diamond-type Si crystal phase, a plurality of Si elements form tetrahedrons. Since the tetrahedrons do not have spaces inside them that can accommodate metal ions such as Li ions, it is difficult to suppress the volume change caused by charging and discharging. On the other hand, compared with silicon inclusion compounds, it has the advantage of low manufacturing cost.
[0058] In the X-ray diffraction measurement using CuKα rays, the diamond-type Si crystal phase has typical peaks at 2θ=28.44°, 47.31°, 56.10°, 69.17°, and 76.37°. These peak positions can move within the range of ±0.50°, ±0.30°, and ±0.10°, respectively.
[0059] The active material in the present disclosure contains at least Si. The active material contains at least Si, and may contain only Si or may further contain other elements. Examples of other elements include metal elements such as Li and Na. Furthermore, elements contained in functional groups or compounds present on the surface of the active material (e.g., O, C, H) are not considered. In addition, the active material may or may not have a SiO skeleton. In addition, for example, in the case where the active material has a crystal phase of a type II silicon inclusion compound, its composition is preferably composed of Nax Si 136 (0≤x≤20). x may be 0 or greater than 0. On the other hand, x may be 10 or less or 5 or less. The composition of the active material can be determined by, for example, EDX, XRD, XRF, ICP, or atomic absorption spectrometry.
[0060] As the shape of the active material in the present disclosure, for example, a granular shape can be cited. The active material can be a primary particle or a secondary particle formed by agglomeration of primary particles. The average particle size of the primary particles is, for example, greater than 50 nm, greater than 100 nm, or greater than 150 nm. On the other hand, the average particle size of the primary particles is, for example, less than 3000 nm, less than 1500 nm, or less than 1000 nm. In addition, the average particle size of the secondary particles is, for example, greater than 1 μm, greater than 2 μm, or greater than 5 μm. On the other hand, the average particle size of the secondary particles is, for example, less than 60 μm, or less than 40 μm. Furthermore, the average particle size can be determined, for example, by SEM observation. The number of samples is preferably large, for example, greater than 20, greater than 50, or greater than 100.
[0061] The active material in the present disclosure preferably has voids inside the primary particles. This is because it can further reduce the volume change during charge and discharge. In particular, the active material preferably has many tiny voids with a pore diameter of less than 100 nm. This is because it can suppress the collapse of voids caused by pressing. The void volume of voids with a pore diameter of less than 100 nm is, for example, more than 0.05cc / g, can be more than 0.07cc / g, or can be more than 0.10cc / g. On the other hand, the above-mentioned void volume is, for example, less than 0.15cc / g. The void volume can be determined, for example, by mercury porosimetry, BET measurement, gas adsorption method, 3D-SEM, and 3D-TEM.
[0062] In the case where the active material in the present disclosure has voids inside the primary particles, the void ratio is, for example, 4% or more, or 10% or more. In addition, the above-mentioned void ratio is, for example, 40% or less, or 20% or less. The void ratio can be calculated, for example, in the following order. First, the electrode layer containing the active material is cross-sectioned by ion milling. Then, the cross section is observed with a SEM (scanning electron microscope) to obtain a photograph of the particles. Image analysis software is used to distinguish the silicon part and the void part from the obtained photograph, and the photograph is binarized. The areas of the silicon part and the void part are calculated, and the void ratio (%) is calculated according to the following formula.
[0063] Void ratio (%) = 100 × (void area) / ((silicon area) + (void area))
[0064] The specific image analysis and calculation of the void ratio can be performed as follows. As the image analysis software, for example, Fiji ImageJ bundled with Java1.8.0_172 (hereinafter referred to as Fiji) is used. The secondary electron image and the reflected electron image of the same field of view are synthesized and converted into RGB color images. Then, in order to remove the noise of each pixel, the obtained RGB image is blurred by the function "Median (filter size = 2)" in Fiji. Next, through the function "Weka Machine Learning" in Fiji, any multiple areas in the image from which the above noise has been removed are designated as silicon parts or void parts by a person, and teacher data for distinguishing between silicon parts and void parts is prepared. Then, based on the prepared teacher data, the silicon part and the gap part are distinguished by a machine in Fiji, and the area ratio of the silicon part and the gap part is calculated.
[0065] Regarding RGB color imaging, since both the secondary electron image and the reflected electron image are expressed in grayscale, for example, the brightness x in each pixel of the secondary electron image is assigned to a Red value, and similarly, the brightness y in the reflected electron image is assigned to a Green value. Thus, for example, for each pixel, RGB imaging is performed as R=x, G=y, and B=(x+y) / 2.
[0066] The detailed conditions in the above "Weka Machine Learning" are as follows. Gaussian blur, Hessian, Membrane projections, Mean, Maximum, Anisotropic diffusion, Sobel filter, Difference of gaussians, Variance, Minimum, and Median are selected as Training features (when creating training data in machine learning, the numerical characteristics of the machine's image are focused on). In addition, as other parameters, Membranethickness is set to 3, Membrane patch size is set to 19, Minimum sigma is set to 1.0, and Maximum sigma is set to 16.0.
[0067] The active material in the present disclosure is generally used in all-solid-state batteries. The active material in the present disclosure may be a negative electrode active material or a positive electrode active material, but the former is preferred. In the present disclosure, an electrode layer (negative electrode layer or positive electrode layer) having the above-mentioned active material and an all-solid-state battery having the electrode layer may also be provided. As a method for producing the active material, for example, the production method described in "C. Production method of active material" described later can be cited.
[0068] B. All-solid-state battery
[0069] Figure 2 This is a schematic cross-sectional view illustrating an all-solid-state battery in the present disclosure. Figure 2 The all-solid-state battery 10 shown has: a positive electrode layer 1, a negative electrode layer 2, a solid electrolyte layer 3 formed between the positive electrode layer 1 and the negative electrode layer 2, a positive electrode collector 4 for collecting current from the positive electrode layer 1, and a negative electrode collector 5 for collecting current from the negative electrode layer 2. In the present disclosure, the negative electrode layer 2 contains the above-mentioned active material and the solid electrolyte.
[0070] According to the present disclosure, by using the above-mentioned active material, it is possible to obtain an all-solid-state battery capable of suppressing the volume change of the negative electrode layer during charge and discharge.
[0071] 1. Negative electrode layer
[0072] The negative electrode layer is a layer containing at least a negative electrode active material and a solid electrolyte. In addition, the negative electrode layer may contain at least one of a conductive material and a binder as needed.
[0073] Regarding the negative electrode active material, the contents are the same as those described in the above-mentioned "A. Active Material", so the description here is omitted. The proportion of the negative electrode active material in the negative electrode layer is, for example, more than 20 weight %, may be more than 30 weight %, or may be more than 40 weight %. If the proportion of the negative electrode active material is too small, sufficient energy density may not be obtained. On the other hand, the proportion of the negative electrode active material is, for example, less than 80 weight %, may be less than 70 weight %, or may be less than 60 weight %. If the proportion of the negative electrode active material is too much, the ionic conductivity and electronic conductivity in the negative electrode layer may be relatively reduced.
[0074] The negative electrode layer may contain at least one of a solid electrolyte, a conductive material and a binder as needed. As a solid electrolyte, for example, the solid electrolyte described in "3. Solid electrolyte layer" described later can be cited. As a conductive material, for example, a carbon material, a metal particle, and a conductive polymer can be cited. As a carbon material, for example, granular carbon materials such as acetylene black (AB), Ketjen black (KB), carbon fibers, carbon nanotubes (CNT), fibrous carbon materials such as carbon nanofibers (CNF) can be cited. In addition, as a binder, for example, a rubber-based binder and a fluoride-based binder can be cited.
[0075] The thickness of the negative electrode layer is, for example, 0.1 μm or more and 1000 μm or less. The negative electrode layer in the present disclosure is generally used in all-solid batteries.
[0076] 2. Positive electrode layer
[0077] The positive electrode layer is a layer containing at least a positive electrode active material. In addition, the positive electrode layer may also contain at least one of a solid electrolyte, a conductive material, and a binder as needed.
[0078] Examples of the positive electrode active material include oxide active materials. Examples of the oxide active material include LiCoO2, LiMnO2, LiNiO2, LiVO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 and other rock salt layered active materials, LiMn2O4, Li4Ti5O 12 、Li(Ni 0.5 Mn 1.5 )O4 and other spinel active materials, LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4 and other olivine active materials.
[0079] A coating layer containing a Li ion conductive oxide can be formed on the surface of the oxide active material. This is because it can inhibit the reaction between the oxide active material and the solid electrolyte (especially the sulfide solid electrolyte). As a Li ion conductive oxide, for example, LiNbO3 can be cited. The thickness of the coating layer is, for example, greater than 1 nm and less than 30 nm. In addition, as a positive electrode active material, for example, Li2S can also be used.
[0080] The solid electrolyte, conductive material and binder used in the positive electrode layer are the same as those described in the above-mentioned "1. Negative electrode layer", and thus are omitted here. The thickness of the positive electrode layer is, for example, 0.1 μm or more and 1000 μm or less.
[0081] 3. Solid electrolyte layer
[0082] The solid electrolyte layer is a layer formed between the positive electrode layer and the negative electrode layer, and contains at least a solid electrolyte.
[0083] As solid electrolytes, inorganic solid electrolytes such as sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and halide solid electrolytes can be cited. As sulfide solid electrolytes, for example, solid electrolytes containing Li element, X element (X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, In) and S element can be cited. In addition, the sulfide solid electrolyte may also contain at least one of O element and halogen element. As halogen elements, for example, F element, Cl element, Br element, and I element can be cited. The sulfide solid electrolyte can be glass (amorphous) or glass ceramic. As sulfide solid electrolytes, for example, Li2S-P2S5, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-SiS2, Li2S-GeS2, and Li2S-P2S5-GeS2 can be cited.
[0084] The thickness of the solid electrolyte layer is, for example, 0.1 μm or more and 1000 μm or less.
[0085] 4. Other structures
[0086] The all-solid battery in the present disclosure preferably has a positive electrode current collector for collecting current in the positive electrode layer and a negative electrode current collector for collecting current in the negative electrode layer. As the material of the positive electrode current collector, for example, SUS, aluminum, nickel, iron, titanium and carbon can be cited. On the other hand, as the material of the negative electrode current collector, for example, SUS, copper, nickel and carbon can be cited.
[0087] The all-solid battery in the present disclosure may also have a constraint fixture, which applies constraint pressure to the positive electrode layer, the solid electrolyte layer and the negative electrode layer in the thickness direction. By using the constraint fixture, a good ion conduction path and an electronic conduction path can be formed. The constraint pressure is, for example, more than 0.1MPa, more than 1MPa, or more than 5MPa. On the other hand, the constraint pressure is, for example, less than 100MPa, less than 50MPa, or less than 20MPa.
[0088] 5. All-solid-state batteries
[0089] The type of all-solid-state battery in the present disclosure is not particularly limited, and a typical example is a lithium-ion battery. In addition, the all-solid-state battery in the present disclosure may be a primary battery or a secondary battery, wherein a secondary battery is preferred. Because it can be repeatedly charged and discharged, it is useful as, for example, a vehicle-mounted battery.
[0090] The all-solid battery in the present disclosure may be a single cell or a stacked battery. The stacked battery may be a monopolar stacked battery (a stacked battery of a parallel type) or a bipolar stacked battery (a stacked battery of a series type). As the shape of the all-solid battery, for example, a coin type, a laminated type, a cylindrical type, and a square type may be cited.
[0091] C. Method for producing active substances
[0092] Figure 3 This is a flow chart illustrating the method for producing the active material in the present disclosure. Figure 3 In the production method shown, first, a first precursor is synthesized, then the first precursor is washed with an organic solvent or acid having a relative dielectric constant of 5 or more to obtain a second precursor, and then the second precursor is dried by heat to obtain a target active material. Figure 4 This is a flow chart illustrating a method for synthesizing the first precursor in the present disclosure. Figure 4In the process, a Zinter compound containing Na and Si and having at least a Zinter phase is prepared, and Na is removed from the Zinter compound, thereby preparing an intermediate having a crystal phase of a type II silicon inclusion compound. Next, the intermediate and a Li-based material are alloyed in a predetermined ratio to obtain an alloy compound (alloying treatment). Next, Li is removed from the alloy compound to form voids inside the primary particles (Li removal treatment). Thus, a first precursor having a crystal phase of a type II silicon inclusion compound is obtained.
[0093] According to the present disclosure, by washing the first precursor with an organic solvent or acid with a high relative dielectric constant and then drying it, an active material capable of suppressing the volume change of the negative electrode layer during charge and discharge can be obtained. It is speculated that if there are, for example, C2H5OH (a compound having an OH group), CH3COONa, or CH3COOLi on the surface of the active material, Si-R (R is a hydrophobic functional group such as CH3) is formed on the surface of the active material in the subsequent drying process, and the polarity of the surface of the active material is reduced. When there are many Si-Rs, I1 becomes larger. In contrast, in the present disclosure, C2H5OH and the like can be removed by treating the surface of the active material with an organic solvent or acid with a high relative dielectric constant. Therefore, even if a drying process is performed, the proportion of Si-R can be reduced. As a result, the proportion of Si-O-Si with high polarity can be increased, and the aggregation of the active material can be suppressed when the electrode layer is made.
[0094] 1. Synthesis process
[0095] The synthesis step in the present disclosure is a step of synthesizing the first precursor. The first precursor corresponds to the active material before the washing step. The first precursor contains at least Si, and may contain only Si, or may also contain other elements. Regarding other elements, it is the same as the contents described in the above-mentioned "A. Active material". In addition, the first precursor preferably has at least one of a type II silicon inclusion compound crystal phase, a type I silicon inclusion compound crystal phase, and a diamond Si crystal phase. In addition, the first precursor preferably has any one of the above-mentioned crystal phases as the main phase.
[0096] The synthesis method of the first precursor is not particularly limited, and may include an alloying treatment step and a Li removal treatment step. The alloying treatment step alloys an intermediate having at least one of a type II silicon inclusion compound crystal phase, a type I silicon inclusion compound crystal phase, and a diamond-type Si crystal phase with a Li-based material to obtain an alloy compound. The Li removal treatment step removes Li from the above alloy compound to form voids inside the primary particle.
[0097] (1) Intermediates
[0098] The intermediate preferably has at least one of a II-type silicon inclusion compound crystal phase, an I-type silicon inclusion compound crystal phase, and a diamond-type Si crystal phase. In addition, the first precursor preferably has any one of the above-mentioned crystal phases as a main phase. For example, as an intermediate having a diamond-type Si crystal phase, commercially available Si particles can be used. On the other hand, an intermediate having a crystal phase of a II-type silicon inclusion compound or a crystal phase of a I-type silicon inclusion compound can be obtained, for example, by a method of removing the above-mentioned Na from a Zinter compound containing Na and Si and having at least a Zinter phase. By adjusting the conditions for removing Na, the ratio of the crystal phase of the II-type silicon inclusion compound and the crystal phase of the I-type silicon inclusion compound can be adjusted. Below, a method for preparing an intermediate having a crystal phase of a II-type silicon inclusion compound or a crystal phase of a I-type silicon inclusion compound is described.
[0099] (i) Making Zintir
[0100] The Zintl compound has a Zintl phase. In the X-ray diffraction measurement using CuKα rays, the Zintl phase has typical peaks at 2θ=16.10°, 16.56°, 17.64°, 20.16°, 27.96°, 33.60°, 35.68°, 40.22°, and 41.14°. These peak positions can move back and forth in the range of ±0.50°, or in the range of ±0.30°. The Zintl compound preferably has a Zintl phase as the main phase. The Zintl compound may have a crystal phase of a type I silicon inclusion compound, or may not have a crystal phase of a type I silicon inclusion compound. In addition, the Zintl compound may have a crystal phase of a type II silicon inclusion compound, or may not have a crystal phase of a type II silicon inclusion compound.
[0101] The composition of the Zintir compound is not particularly limited, but preferably Na z Si 136 The composition (121≤z≤151) is represented. z may be 126 or more, or 131 or more. On the other hand, z may be 141 or less.
[0102] The Zintir compound can be obtained, for example, by heat treating a raw material mixture containing Na (single substance) and Si (single substance). The ratio of Na (single substance) to Si (single substance) is not particularly limited, and the Na (single substance) can be, for example, 0.8 mol parts or more, or 1 mol parts or more relative to 1 mol part of Si (single substance). On the other hand, the Na (single substance) can be, for example, 1.5 mol parts or less, or 1.3 mol parts or less relative to 1 mol part of Si (single substance).
[0103] The heat treatment temperature is, for example, 500° C. to 1000° C. In addition, the heat treatment time is, for example, 1 hour to 50 hours. In particular, the heat treatment is preferably performed at about 700° C. (for example, 650° C. to 750° C.) and for about 20 hours (for example, 15 hours to 25 hours).
[0104] (ii)Na removal
[0105] As a method for removing Na from the Zintel compound, for example, heat treatment can be cited. The heat treatment temperature is, for example, above 280°C, and can be above 300°C. On the other hand, the heat treatment temperature is, for example, below 500°C. The heat treatment time is, for example, above 1 hour and below 50 hours. The heat treatment can be carried out under a normal pressure atmosphere or under a reduced pressure atmosphere. In the latter case, the pressure during the heat treatment is, for example, below 10Pa, below 1Pa, or below 0.1Pa. In addition, the heat treatment can be carried out under an inert atmosphere such as an Ar atmosphere.
[0106] (iii) Intermediates
[0107] The composition of the intermediate obtained by the above method is not particularly limited, but preferably Na y Si 136 (0≤y≤24). y may be 0 or greater than 0. On the other hand, y may be 20 or less or 10 or less.
[0108] (2) Alloying treatment
[0109] The alloying treatment in the present disclosure is a treatment for alloying the above-mentioned intermediate with a Li-based material to obtain an alloy compound.
[0110] The Li-based material is not particularly limited as long as it is a material that can be alloyed with the intermediate, and can be a simple Li or a Li alloy. The Li alloy is preferably an alloy with Li as the main component. Because it is easy to alloy with the intermediate. As a method for alloying the intermediate and the Li-based material, for example, a method of mixing the two and a method of heat treating the two can be cited.
[0111] In the alloying process, the molar ratio (Li / Si) of Li contained in the Li-based material relative to Si contained in the intermediate is preferably set to a predetermined range, and the intermediate and the Li-based material are alloyed. Li / Si is, for example, more than 0.5, can be more than 0.75, or can be more than 1. If Li / Si is too small, it is possible that no voids are formed inside the primary particle. On the other hand, Li / Si is, for example, less than 3, can be less than 2.5, or can be less than 2. If Li / Si is too large, it may be impossible to maintain the desired crystalline phase. By alloying with Li, there is a tendency for the crystallinity of Si to decrease, so it is preferred to control Li / Si.
[0112] (3) Li removal treatment
[0113] The Li removal step in the present disclosure is a step of removing Li from the alloy compound to form voids inside the primary particles. By removing Li (highly dispersed Li) contained in the alloy compound, voids of nanometer size (nanoscale) can be formed.
[0114] As a method for removing Li from an alloy compound, for example, a method of reacting a Li extractant with an alloy compound can be cited. The Li extractant is, for example, a liquid. As a Li extractant, for example, primary alcohols such as methanol, ethanol, 1-propanol, 1-butanol, 1-pentanol, 1-hexanol, secondary alcohols such as 2-propanol, 2-butanol, 2-pentanol, 2-hexanol, tertiary alcohols such as ... In the present disclosure, two or more Li extracting agents may be used. In this case, the two or more Li extracting agents may be mixed and used, or may be used separately (two or more stages of treatment may be performed as Li removal).
[0115] The Li extracting agent preferably has a small amount of water. If the amount of water is too much, the alloy compound may deteriorate. The amount of water contained in the Li extracting agent is, for example, 100 ppm or less, or 10 ppm or less. The weight ratio of the Li extracting material to the alloy compound is, for example, 5 or more, 10 or more, or 15 or more. In addition, the above weight ratio is, for example, 500 or less, or 250 or less.
[0116] The method for reacting the Li extractant with the alloy compound is not particularly limited. The Li extractant can be directly contacted with the alloy compound, or the Li extractant can be contacted with a dispersion in which the alloy compound is dispersed. As a dispersion medium, for example, saturated hydrocarbons such as n-heptane, n-octane, n-decane, 2-ethylhexane, cyclohexane, unsaturated hydrocarbons such as hexene and heptene, 1,3,5-trimethylbenzene, toluene, xylene, ethylbenzene, propylbenzene, isopropylbenzene, 1,2,4-trimethylbenzene, 1,2,3-trimethylbenzene and other aromatic hydrocarbons, n-butyl ether, n-hexyl ether, isopentyl ether, diphenyl ether, methyl phenyl ether, cyclopentyl methyl ether and other ethers can be cited. The relative dielectric constant of the dispersion medium is, for example, less than 3.08, or less than 3.00. On the other hand, the relative dielectric constant of the dispersion medium is, for example, more than 1.50, or more than 1.70. The relative dielectric constant can be measured, for example, by the method described in JIS C 2565 (void resonator method, etc.).
[0117] 2. Washing process
[0118] The washing step in the present disclosure is a step of washing the first precursor with an organic solvent or acid having a relative dielectric constant of 5 or more to obtain a second precursor. The second precursor corresponds to the active material after the washing step and before the drying step. In addition, the second precursor and the first precursor usually have the same crystal phase.
[0119] The relative dielectric constant (25° C.) of the organic solvent or acid is usually 5 or more, and may be 10 or more, or 15 or more. Examples of the organic solvent include ketones such as acetone, methyl ethyl ketone, and diethyl ketone, alcohols such as ethanol, methanol, and propanol, esters such as methyl acetate, ethyl acetate, butyl acetate, and butyl butyrate, and ethers such as diethyl ether and dibutyl ether. In addition, aromatic hydrocarbons may be used as the organic solvent. On the other hand, examples of the acid include inorganic acids such as hydrochloric acid, sulfuric acid, and nitric acid.
[0120] As a method for washing the first precursor with an organic solvent, for example, a method of immersing the first precursor in an organic solvent can be cited. In this case, ultrasonic treatment can also be performed. In addition, washing can also be performed by spraying an organic solvent onto the first precursor. The washing time is not particularly limited, for example, it is 10 minutes or more and 10 hours or less. In the infrared spectrum, the second precursor can be -1 Above and 3500cm -1 Below there is a peak derived from -OH.
[0121] 3. Drying process
[0122] The drying step in the present disclosure is a step of drying the second precursor by heat to obtain the active material. The drying step is a step of removing the organic solvent or acid from the second precursor. In addition, for example, when the second precursor contains Na, Na may or may not be removed from the second precursor in the drying step.
[0123] The drying temperature is, for example, 280°C or more, or 300°C or more. On the other hand, the drying temperature is, for example, 500°C or less. The drying time is, for example, 1 hour or more and 50 hours or less. Drying can be carried out in a normal pressure atmosphere or in a reduced pressure atmosphere. In the latter case, the pressure during drying is, for example, 10Pa or less, 1Pa or less, or 0.1Pa or less. In addition, drying can be carried out in an inert atmosphere such as an Ar atmosphere. In addition, as a drying method, for example, a method using a sintering furnace can be cited.
[0124] 4. Active substances
[0125] The active material obtained by the above steps is the same as that described in the above-mentioned "A. Active material", and thus the description thereof is omitted here.
[0126] The present disclosure is not limited to the above-mentioned embodiments. The above-mentioned embodiments are illustrative, and all schemes having substantially the same technical concept as that described in the claims of the present disclosure and having the same functions and effects are included in the technical scope of the present disclosure.
[0127] [Example]
[0128] [Example 1]
[0129] (Synthesis of active substances)
[0130] Si particles and Na particles were mixed in a molar ratio of 1:1, put into a crucible, sealed in an Ar atmosphere, and heated at 700°C to synthesize NaSi (Zinter compound). Then, Na was removed by heating at 340°C under vacuum (about 1 Pa) to obtain an intermediate. The obtained intermediate and Li metal were weighed at a molar ratio of Li / Si=1, mixed in a mortar under an Ar atmosphere, and an alloy compound was obtained. The obtained alloy compound was reacted with ethanol under an Ar atmosphere to form voids inside the primary particles, and the first precursor was obtained. In addition, the ratio of the alloy compound to ethanol is based on a weight ratio, and the alloy compound: ethanol = 12:400.
[0131] Next, the obtained first precursor was washed. Specifically, it was immersed in acetone and subjected to ultrasonic treatment for 30 minutes using an ultrasonic device (US-3KS manufactured by SND) to obtain a second precursor. Then, it was dried at 430° C. for 6 hours using a calcining furnace to obtain an active material.
[0132] (Production of negative electrode)
[0133] The obtained active material, sulfide solid electrolyte (Li2S-P2S5 glass ceramic), conductive material (VGCF), butyl butyrate solution containing PVDF binder at a ratio of 5% by weight, and butyl butyrate were added to a polypropylene container and stirred for 30 seconds with an ultrasonic dispersion device (UH-50 made by SMT). Next, the container was vibrated for 30 minutes with a vibrator (TTM-1 made by Shibata Science Co., Ltd.). Using an applicator, the scraper method was used to apply it to the negative electrode collector (Cu foil, made by UACJ) and dried on a hot plate at 100°C for 30 minutes. Thus, a negative electrode having a negative electrode collector and a negative electrode layer was obtained.
[0134] (Production of positive electrode)
[0135] The positive electrode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, average particle size 6μm), sulfide solid electrolyte (Li2S-P2S5 glass ceramic), conductive material (VGCF), butyl butyrate solution containing PVDF-based binder at a ratio of 5% by weight, and butyl butyrate, are stirred for 30 seconds using an ultrasonic disperser (UH-50 made by SMT). Next, the container is vibrated for 3 minutes using a vibrator (TTM-1 made by Shibata Science Co., Ltd.). Using an applicator, apply it to the positive electrode collector (Al foil, made by Showa Denko) using a scraper method and dry it on a hot plate at 100°C for 30 minutes. Thus, a positive electrode having a positive electrode collector and a positive electrode layer is obtained. Furthermore, the area of the positive electrode is smaller than that of the negative electrode.
[0136] (Fabrication of Solid Electrolyte Layer)
[0137] A sulfide solid electrolyte (Li2S-P2S5 glass ceramic), a heptane solution containing a butadiene rubber-based binder at a ratio of 5% by weight, and heptane were added to a polypropylene container and stirred for 30 seconds with an ultrasonic disperser (UH-50 made by SMT). Next, the container was vibrated for 30 minutes with a vibrator (TTM-1 made by Shibata Science Co., Ltd.). Using an applicator, a scraper method was used to apply it to a release sheet (Al foil) and dried on a hot plate at 100°C for 30 minutes. Thus, a transfer member having a release sheet and a solid electrolyte layer was obtained.
[0138] (Fabrication of all-solid-state batteries)
[0139] A solid electrolyte layer for bonding was placed on the positive electrode layer of the positive electrode, and the mixture was placed in a roll press and pressed at 20 kN / cm (about 710 MPa) and 165° C. Thus, a first laminate was obtained.
[0140] Next, the negative electrode is placed in a roller press and pressed at 20 kN / cm (about 630 MPa) and 25°C. Then, the solid electrolyte layer for bonding and the transfer member are sequentially arranged from the negative electrode layer side. At this time, the solid electrolyte layer for bonding and the solid electrolyte layer in the transfer member are arranged in an opposing manner. The obtained laminate is placed in a flat uniaxial press and temporarily pressed at 100 MPa and 25°C for 10 seconds. Then, the peeling sheet is peeled off from the solid electrolyte layer. Thus, the second laminate is obtained.
[0141] Next, the solid electrolyte layer for bonding of the first stack and the solid electrolyte layer of the second stack were arranged to face each other, placed on a flat uniaxial press, and pressed at 200 MPa and 135° C. for 1 minute. Thus, an all-solid-state battery was obtained.
[0142] [Example 2]
[0143] An active material was obtained in the same manner as in Example 1 except that the ratio of the alloy compound to ethanol was changed to alloy compound:ethanol=1:150 in weight ratio. An all-solid-state battery was obtained in the same manner as in Example 1 using the obtained active material.
[0144] [Comparative Examples 1 and 2]
[0145] An active material was obtained in the same manner as in Examples 1 and 2 except that the first precursor was not washed. An all-solid-state battery was obtained in the same manner as in Example 1 using the obtained active material.
[0146] [Comparative Example 3]
[0147] A full solid-state battery was obtained in the same manner as in Example 1 except that commercially available Si particles (diamond-type Si particles) were used.
[0148] [evaluate]
[0149] (IR measurement)
[0150] The active materials obtained in Examples 1 and 2 and Comparative Examples 1 to 3 were subjected to infrared spectroscopy (IR) measurement. The IR measurement was performed by a single reflection ATR method (ATR accessory: Thunderdome manufactured by SpectraTech), a DTGS detector, and a frequency resolution of 4 cm. -1 The results are shown in Table 1 and Figure 5 .
[0151] (Determination of the increase in restraint pressure)
[0152] The all-solid batteries obtained in Examples 1, 2 and Comparative Examples 1 to 3 were charged and the increase in the constraint pressure was measured. The test conditions were a constraint pressure (standard size) of 5 MPa, a charge of 0.1C, and a cutoff voltage of 4.55 V. The constraint pressure at 4.55 V was measured to determine the increase in the constraint pressure from the state before charging. The results are shown in Table 1. The results of the increase in the constraint pressure in Table 1 are relative values when the results of Comparative Example 1 are set to 100.
[0153] (XRD measurement)
[0154] X-ray diffraction (XRD) using CuKα rays was performed on the active materials obtained in Examples 1 and 2 and Comparative Examples 1 and 2. As a result, it was confirmed that the active materials obtained in Examples 1 and 2 and Comparative Examples 1 and 2 had a crystal phase of type II silicon inclusion compound as a main phase.
[0155] In addition, the intensity of the peak A located near 2θ=20.09° in the crystal phase of the type II silicon inclusion compound is defined as I A The intensity of peak B near 2θ = 31.72° is defined as I B In addition, the maximum intensity at 2θ = 22° to 23° is defined as I M , find I A / I M and I B / I M The results are shown in Table 1.
[0156] (Determination of void volume)
[0157] The void volume (void volume of voids with a pore diameter of 100 nm or less) of the active materials obtained in Examples 1 and 2 and Comparative Examples 1 and 2 was determined. The void volume was measured using a mercury intrusion meter. The measuring device used was Pore Master 60-GT (QuantaChrome). The analysis was performed using the Washburn method. The results are shown in Table 1.
[0158] (SEM measurement)
[0159] The active materials obtained in Examples 1 and 2 and Comparative Examples 1 and 2 were subjected to SEM-EDX (scanning electron microscope-energy dispersive X-ray spectroscopy) measurement. As a result, it was confirmed that the active materials obtained in Examples 1 and 2 had nano-sized voids formed inside the primary particles.
[0160] Table 1
[0161]
[0162] As shown in Table 1 and Figure 5 As shown, it is confirmed that the values of I2 / I1 of Examples 1 and 2 are large and the increase in the constraint pressure is significantly small compared with Comparative Examples 1 and 2. Specifically, the increase in the constraint pressure of Examples 1 and 2 is reduced by more than 70% compared with Comparative Example 1. It is speculated that this is because the polarity of the surface of the Si particles is high, and thus the affinity with the solid electrolyte with high polarity is generally good, and the Si particles are evenly dispersed when the negative electrode layer is made. In addition, it is estimated that since the Si particles are evenly dispersed, the contact area between the Si particles and the solid electrolyte is increased, so that the charge and discharge reaction in the negative electrode layer is uniform, and as a result, the volume change of the negative electrode can be suppressed. On the other hand, in Comparative Example 3, although the value of I2 / I1 is large, the values of I2 and I1 are small, and the increase in the constraint pressure is also large.
[0163] In addition, in Examples 1 and 2 and Comparative Examples 1 and 2, I A / I M The value and I B / I M The values of are all greater than 1, confirming that a crystal phase of type II silicon inclusion compound has been formed. B / I M The value of is less than 1, and the crystal phase of type II silicon inclusion compound is not formed.
Claims
1. An active material for an all-solid-state battery, comprising at least Si, In infrared spectroscopy, at 900 cm -1 Over 950cm -1 The maximum peak intensity below is set as I1, and 1000cm -1 Over 1100cm -1 When the following maximum peak intensity is set as I2, I1 and I2 satisfy 0.55≤I2 / I1≤1.0 and 0.01≤I1, I1 is a peak derived from Si—R present on the surface of the active material, and R is a hydrophobic functional group. 2 . The active material according to claim 1 , wherein I1 satisfies 0.02≤I1≤0.
08.
3. An active material for an all-solid-state battery, comprising at least Si, In infrared spectroscopy, at 900 cm -1 Over 950cm -1 The maximum peak intensity below is set as I1, and 1000cm -1 Over 1100cm -1 When the following maximum peak intensity is set as I2, I1 and I2 satisfy 0.55≤I2 / I1≤1.0 and 0.01≤I2, I1 is a peak derived from Si—R present on the surface of the active material, and R is a hydrophobic functional group. The active material according to claim 3 , wherein I2 satisfies 0.02≤I2≤0.
08. 5 . The active material according to claim 1 , comprising at least one of a crystal phase of a type II silicon clathrate, a crystal phase of a type I silicon clathrate, and a diamond-type Si crystal phase. 6 . The active material according to claim 1 , which has voids inside primary particles. The active material according to claim 5 , wherein the active material has voids inside primary particles.
8. An all-solid-state battery comprising a positive electrode layer, a negative electrode layer, and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer, The negative electrode layer contains the active material according to any one of claims 1 to 7 and a solid electrolyte.
9. A method for producing an active material, comprising a synthesis step, a washing step and a drying step, In the synthesis step, a Zinter compound containing Na and Si and having at least a Zinter phase is prepared, and Na is removed from the Zinter compound to obtain an intermediate having a crystal phase of a type II silicon clathrate, the intermediate is alloyed with a Li-based material to obtain an alloy compound, Li is removed from the alloy compound to form voids inside primary particles, thereby obtaining a first precursor having a type II silicon clathrate crystal phase, and when the intermediate is alloyed with the Li-based material, a molar ratio of Li contained in the Li-based material to Si contained in the intermediate, Li / Si, is in a range of 0.5 or more and 3 or less, In the washing step, the first precursor is washed with an organic solvent or an acid having a relative dielectric constant of 5 or more to obtain a second precursor. In the drying step, the second precursor is dried by heat to obtain the active material. 10 . The method for producing an active substance according to claim 9 , wherein the organic solvent is a ketone. 11 . The method for producing an active material according to claim 9 , wherein in the Li removal treatment step, ethanol is used to remove the Li from the alloy compound.
Citation Information
Patent Citations
Negative electrode active material for lithium ion secondary battery
JP2011108635A
Negative electrode for sulfide all-solid battery, and sulfide all-solid battery and manufacturing method of the same
JP2018142431A
Silicon-based nanoparticle-containing hydrogen polysilsesquioxane, silicone oxide structure, and manufacturing method therefor
JP2019119638A
Negative electrode active material for nonaqueous electrolyte secondary batteries, negative electrode for nonaqueous electrolyte secondary batteries using said negative electrode active material, and nonaqueous electrolyte secondary battery using said negative electrode
WO2014119238A1
Method for producing active material, active material and battery
US20200119352A1